Pengaruh Dukungan Sosial Terhadap Optimisme Masa Depan Anak Berhadapan Dengan Hukum (ABH) Di Jabodetabek - Adelya Shofa Anisa; Neneng Tati Sumiati (Psikologi Prima, 2024)
Seeing the number of Children Against the Law (ABH) in Indonesia and the importance of optimism for the future of ABH, this study aims to examine the effect of social support on the future optimism of Children Against the Law in Jabodetabek. The research method used was quantitative, involving 176 Children Against the Law (ABH) categorized as perpetrators in Jabodetabek selected through non-probability sampling techniques, specifically purposive sampling. The questionnaire used contains modifications of the Life Orientation Test-Revised (LOT-R) measuring instrument and instruments compiled by researchers based on the theory of Sarafino and Smith (2011). Test the validity of each questionnaire item using Confirmatory Factor Analysis (CFA), while Multiple Regression Analysis tests the effect of independent variables on the dependent variable. The results showed that ABH's future optimism was significantly influenced by social support by 43.4%. However, based on hypothesis testing regarding the significance of each independent variable regression coefficient, only two social support variables significantly influenced optimism, namely emotional support (sig. 0.029 < 0.05) and information support (sig. 0.00 < 0.05). In contrast, instrumental support and friendship did not significantly influence optimism. The results of this study can be used as a basis for creating programs aimed at increasing ABH's future optimism.